Malignant spinal cord compression secondary to testicular seminoma at the time of initial presentation and at relapse while on surveillance - Yee, Don; Gabos, Zsolt; North, Scott; Moore, Ronald B. (Canadian Urological Association Journal, 2012)
We report cases of 2 pure seminoma patients who developed metastatic spinalcord compressions. One patient was diagnosed at age 33 years with stage 1seminoma and, after undergoing an orchidectomy, chose to be followed ona surveillance protocol. He was lost to follow-up and presented again 22months later with back pain, leg weakness and sensory loss when his diseaserecurred as a spinal cord compression. He was treated with urgent surgicaldecompression and subsequent standard chemotherapy. More than 2years posttreatment, he is disease-free with normal neurologic function inhis lower extremities. The second patient presented at age 44 years withback pain and rapid loss of leg strength and sensation. Investigations revealeda malignant cord compression with lymphatic and vertebral body metastases.On physical examination, the patient was found to have a 6-cm lefttesticular mass. He was treated with emergency radiotherapy to the regionof his cord compression followed by a left inguinal orchidectomy. Pathologyconfirmed a pure classic seminoma. Postoperatively, he received standardchemotherapy and eventually regained neurologic function in his legs. Althoughit is rare for malignant spinal cord compression to occur in seminoma patients—either as the initial presentation of disease or as a site of disease recurrencein stage 1 patients on surveillance—it is crucial to consider seminoma as apossible etiology in young men diagnosed with malignant spinal cord compressionbecause timely contemporary treatments for seminoma will cure mostof these patients and offer them excellent functional recovery.